TINGKAT KESEJAHTERAAN KELUARGA PETANI BUAH DI DESA KOLONGAN KECAMATAN TALAWAAN KABUPATEN MINAHASA UTAR - Kandowangko, Nicolas (HOLISTIK, Journal Of Social and Culture, 2011)
Fruit farmer in the Kolongan Village of Talawaan Sub-district initially oriented on coconut farming. By the development of market demand of local fruits such as duku and rambutan hence most farmers divert their efforts to the local fruit farm. The formulation of the problem studied in this research is the level of welfare of farmers associated with the technical management of fruit farming fruit under is management The results showed that farmer depelopment technical management in Kolongan Village of Sub-disrict Talawaan is based on the traditional approach. Fruit farmer development is still emphasis on local fruit and the are using is still traditional fertilizer. The welfare level of fruit farmer of Kolongan Village Of Talawaan Sub-district, according Sajogjo, already above the poor line. Their average income is four hundred thousand rupiah per month. Prospect and development of because the increase number of population so the need for fruits also increase. The society incomeÂ  is increasing by the development of economic in other sectors so the society afford to buy of agribusiness. Keywords : Management, The Level of Welfare, Potential